Development of Jono Oge ‘Walking House’ Liquefaction Media for Science Learning and Mitigation - Unggul Wahyono; Ketut Alit Adi Untara; Marungkil Pasaribu; Moh Syarif (Jurnal Penelitian Pendidikan IPA, 2025)
When an earthquake occurs, there is a strange phenomenon, namely the liquefaction of large areas of land. The liquefaction of the soil caused the houses to sink into the ground along with the casualties. In addition, there were also houses that shifted hundreds of metres from their initial position because the foundation soil was liquid and was on a slope so that it was like a ‘walking house’ After this phenomenon occurred and the peak of the earthquake had ended, the soil under the foundation of the house that shifted gradually solidified again as before. In science, this phenomenon is called liquefaction. Liquefaction is a phenomenon in which the soil loses much of its strength and stiffness in a short period of time. The soil contracts at the onset of cyclic loading due to earthquake shaking, so that the pore water pressure increases to near or beyond its normal stress. In order for a stable building to stand on the ground, the soil layer must be safe from liquefaction hazards. Seeing the above phenomena and problems, as a researcher in the field of education, it is appropriate to conduct research in the form of developing props for the phenomenon of ‘walking houses’ during liquefaction for science learning. The development research that will be carried out has a problem formulation, namely how to develop teaching aids for the ‘walking house’ phenomenon. The purpose of the research is to develop props for the phenomenon of ‘walking houses’ during liquefaction for science learning. As well as providing an understanding that the phenomenon of walking houses and trees is a natural scientific event that can occur in liquefied areas. This development research uses the 4D model. The 4D model used has several stages, defining, designing, developing, and disseminating. The results of the research on the development of props for the walking house phenomenon can provide a complete scientific understanding of how the house can walk or move when liquefaction occurs while some other houses collapse and sink. The results of this research can also be used for disaster learning so as to provide in-depth knowledge for all students so that in the event of a disaster they are expected to take appropriate and accurate action which in turn can reduce the number of casualties. Based on the normal gains of the application of the ‘walking house’ props for science learning and mitigation at SMPN1 Sigi 0.31 SMPN 13 by 0.33 Sigi SMPN 27 Petobo by 0.19 and SMPN 21 Petobo by 0.32 Petobo said the ‘walking house’ props are effective for science learning and mitigatio